Is cuteness irresistible? The impact of cuteness on customers' intentions to use AI applications. (June 2022) - Lv, Xingyang; Luo, Jingjing; Liang, Yuqing; Liu, Yuqing; Li, Chunxiao
Abstract: Artificial intelligence technology has been increasingly applied in the hospitality and tourism industry, and it is a matter of concern how to increase customer adoption of AI applications in service encounters. This study examines how cuteness of AI applications interacts with the type of service task (emotional or knowledge-based) in their influence on customers' willingness to use the application. Hypotheses were tested using four experiments in different interactive contexts. It was found that customers were more willing to adopt AI applications with high perceived cuteness to perform emotional tasks, and social distance played a mediating role; conversely, customers preferred AI applications with low perceived cuteness to perform knowledge-based tasks, and here performance expectancy mediated the relationship between perceived cuteness and customers' willingness to use the application. The findings advance the theories of customer adoption by revealing and differentiating the "cuteness effect" within different service types.